Long-Term Safety of Ixekizumab Treatment in Patients with Psoriasis, Psoriatic Arthritis, or Axial Spondyloarthritis: a Post Hoc Analysis of Cerebro-Cardiovascular Events - Mark Lebwohl; Atul Deodhar; Sergio Schwartzman; Carlo Salvarani; Meghan Feely McDonald; Natalia Bello; Elsie L. Grace; Elsa Inman; Andris Kronbergs; Marcus Ngantcha; Proton Rahman; Kim A. Papp; et al. (Dermatology and Therapy)
Abstract Introduction Psoriasis (PsO), psoriatic arthritis (PsA), and axial spondyloarthritis (axSpA) may confer an increased risk for cardiovascular (CV) disease, including major adverse cerebro-cardiovascular events (MACE), deep vein thrombosis (DVT), and pulmonary embolism (PE). Patients with these conditions are often exposed for extended time periods to biologics, such as ixekizumab (IXE). Therefore, understanding the risk of CV events, especially MACE, in patients with PsO, PsA, and axSpA exposed to IXE is important. Methods The incidence of MACE (i.e., adjudicated cardiovascular death, non-fatal myocardial infarction, and non-fatal stroke), DVT, and PE was assessed in adults who received ≥ 1 dose of IXE across 25 randomized clinical trials (17 PsO, 4 PsA, 4 axSpA). Rates of CV events were analyzed for pooled studies by indication and analyzed from treatment initiation up to the end of the study program. Exposure-adjusted incidence rates per 100 patient-years (IR/100 PY) are reported. Results This integrated safety analysis included 6892 patients with PsO, 1401 with PsA, and 932 with axSpA. The median duration of IXE exposure was 478.5 days (1.3 years) for patients with PsO, 504.5 days (1.4 years) for patients with PsA, and 981.0 days (2.7 years) for patients with axSpA. The incidence of adjudicated MACE was low (IR/100 PY: PsO = 0.5; PsA = 0.5; axSpA = 0.3) and stable over the treatment periods. The most common types of MACE reported were non-fatal myocardial infarction (IR/100 PY: PsO = 0.3; PsA = 0.3; axSpA = 0.3), followed by non-fatal stroke (IR/100 PY: PsO = 0.1; PsA = 0.2; axSpA = 0.0), and cardiovascular death (IR/100 PY: PsO = 0.1; PsA = 0.1; axSpA = 0.0). The incidences of DVT (IR/100 PY: PsO = 0.1; PsA = 0.1; axSpA = 0.1) and PE (IR/100 PY: PsO = 0.1; PsA = 0.0; axSpA = 0.0) were low. Conclusion This integrated safety analysis of 25 randomized clinical trials showed that the incidence of adjudicated MACE was low among adult patients with PsO, PsA, and axSpA and that the rates did not increase with increasing IXE exposure. Trial Registration The supplementary Table S1 provides a comprehensive list of clinical trials and their registration numbers.